可手术的非小细胞肺癌患者贫血的发生和预后的生存分析 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: The patients with non-small cell lung cancer (NSCLC) might contract anemia, however, whether anemia is one of the independent prognostic factors to the patients with NSCLC is still controversial. So the aim of this study is to investigate the correlation between anemia and overall survival (OS) in patients with NSCLC. METHODS: 1 018 patients with operable NSCLC were retrospectively analyzed in our hospital from January 2000 to December 2008. RESULTS: The occurrence of anemia before operation was 252/1 018 (24.1%). The OS in NSCLC patients without anemia was (2 425.98±50.03) days, and the OS in patients with anemia was (2 107.15±93.86) days. There was significant difference in the OS between them (P=0.001). The patients with anemia in stage Ⅰ had shorter survival time than those without anemia (P < 0.001). But there was no difference in other stage patients. TNM stage, gender, tumor size and lymph nodes metastasis were correlated with OS using Cox regression analysis. CONCLUSION: Anemia is correlated with survival in operable NSCLC patients. Moreover, it is an independent prognostic factor in NSCLC patients with stage Ⅰ.